2002
DOI: 10.1890/0012-9658(2002)083[1271:tiomif]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Meiofauna in Food Webs: Evidence From an Acid Stream

Abstract: Seasonal food webs were constructed for the whole invertebrate assemblage (meio‐ and macrofauna) inhabiting Broadstone Stream (southeast England). High and uniform taxonomic resolution was applied in a dietary analysis, by resolving the complete benthic community to species, including the meiofauna, protozoa, and algae. Meiofauna accounted for 70% of all species in the summary web and for 73% and 63% of those in the summer/autumn and spring webs, respectively. The web structure changed between summer/autumn an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
101
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 67 publications
(133 reference statements)
4
101
0
Order By: Relevance
“…Decreasing connectance with food web size has been documented previously [83], [84] and seems to hold true across lotic ecosystems. The largest food webs typically had connectance values of <0.10, compared to 0.14–0.19 in the Ödenwinkelkees river (excluding 2006).…”
Section: Discussionmentioning
confidence: 63%
“…Decreasing connectance with food web size has been documented previously [83], [84] and seems to hold true across lotic ecosystems. The largest food webs typically had connectance values of <0.10, compared to 0.14–0.19 in the Ödenwinkelkees river (excluding 2006).…”
Section: Discussionmentioning
confidence: 63%
“…Inferring feeding links from prior knowledge, as used here when constructing the binary networks, is a common technique in food web research but has been criticised. Some have claimed that inferring links may overestimate diet breadth (Hall and Raffaelli 1997; Raffaelli 2007) but, conversely, reliance only on directly observed links certainly creates the opposite bias because large numbers of guts are needed to characterise fully the diet of each taxon (especially for predators) and, consequently, the trophic network as a whole (Schmid-Araya et al 2002; Raffaelli 2007; Ings et al 2009; but see Woodward et al 2005). Consequently, inferred feeding links were integrated with directly observed data in our study in order to facilitate comparisons among food webs that were constructed in a consistent and standardised manner.…”
Section: Discussionmentioning
confidence: 99%
“…However, most stream food webs have been constructed with emphasis only upon macroinvertebrates (Closs & Lake 1994;Tavares-Cromar & Williams 1996;Corigliano & Malpassi 1998;Thompson & Townsend 1999). Recently, two studies demonstrated the importance of meiofauna in the structure of a stream food web (Schmid-Araya & Schmid 2000;Schmid-Araya et al 2002a). The inclusion of meiofauna resulted in an increase of web complexity, and consequently caused modifications in the food web patterns.…”
Section: Discussionmentioning
confidence: 99%
“…1993; Thompson & Townsend 2000). In recent years food webs constructed with a higher taxonomic resolution (Hall & Raffaelli 1991;Martinez 1991;Tavares-Cromar & Williams 1996;Schmid-Araya et al . 2002a) invalidated some earlier generalizations and showed that features such as long food chain and omnivory are common in food web structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation